An analysis of factors influencing the use of online loan applications among university students in Jakarta - Azima, Fauzan Zulfa Zian; Kurniawan, Yohannes (Edelweiss Applied Science and Technology, 2025)
Financial structures have changed as a result of the fintech industry's explosive rise in online lending, which provides quick and easy loans that are especially attractive to younger generations. However, there are disadvantages associated with this ease, such as increased debt and concerns about data security. With a focus on digital financial literacy and perceived security threats among DKI Jakarta students, this study investigates the factors influencing the use of online lending services. It incorporates these ideas into a modified UTAUT2 model, which is unique. Partial Least Squares Structural Equation Modeling (PLS-SEM), a quantitative method, was used to examine data from an online survey of 414 Indonesian online lenders. The findings show that behavioral intention is significantly and positively impacted by Hedonic Motivation, Price Value, Digital Financial Literacy, Habit, Effort Expectancy, Social Influence, Performance Expectancy, and Facilitating Conditions. Perceived security risk did not have a substantial impact, which was unexpected. According to these results, in order to increase user adoption and usage, online lenders should prioritize factors such as price competitiveness, social media influence, habit development, user-friendliness, benefits, and easily accessible digital financial literacy materials.